Financial literacy of lusophone university students: Evidence from a university in the interior of Ceará, Brazil (Research, Society and Development, 2021)
Financial aid is provided to students, but like any policy it must be monitored and evaluated. To establish the profile, habits and the way these resources are managed, it is necessary to know the degree of financial literacy of the beneficiaries. The financial literacy rate of 211 students (Portuguese-speaking nationals and foreigners, from Unilab campuses, in the interior of Ceará), was calculated, representing 10.5% of the beneficiaries in 2018. Quantitative and descriptive case study. The methodology for constructing the questionnaire and calculating the indexes was based on the OECD/INFE (2018). The possible influences of socioeconomic and demographic variables on literacy were investigated through Automatic Linear Modeling, using all subsets of the possible predictors of the model; after ensuring normality (Shapiro-Wilk) and absence of correlations (Pearson). It was found 0.68 for behavior, 0.41 for attitude and 0.23 for financial knowledge, considered low, especially financial knowledge. The variables that most affected the results were course, religion and age. In conclusion, the study suggests that efforts should be made in continuing financial education programs.